Why послушать, but услышать? - Nesset, Tore; Janda, Laura A.; Kuznetsova, Julia; Lyashevskaya, Olga; Makarova, Anastasia; Sokolova, Svetlana (Poljarnyj vestnik, 2008)
This article provides a preliminary analysis of aspectual prefixation of Russian perception verbs. It is argued that the choice of prefix is not arbitrary, but depends on the meaning of the verb stem.